Catalytic enhancement of hydrogenation reduction and oxygen transfer reaction for perchlorate removal: A review. (December 2021) - Wang, Bei; Zhai, Yunbo; Li, Shanhong; Li, Caiting; Zhu, Yun; Xu, Min
Abstract: Perchlorate is the main contaminant in surface water and groundwater, and it is of current urgency to remove due to its high water solubility, mobility, and endocrine-disrupting properties. The conversion of perchlorate into harmless chloride ions by using appropriate catalysts is the most promising and effective route to overcome its high activation energy and kinetic stability. Perchlorate is usually reduced in two ways: (1) indirect reduction via oxygen atom transfer (OAT) reaction or (2) hydrodeoxygenation through highly active reducing H atoms. This paper discusses the mechanisms underlying both the OAT reaction catalyzed by homogenous rhenium-oxo complexes or biological Mo-based enzymes and the heterogeneous hydrogenation for perchlorate reduction. Particular emphasis is placed on the factors affecting the catalytic process and the synergy between the (1) and (2) reactions. For completeness, the applicability of different electrolysis devices, electrodes, and bioreactors is also illustrated. Finally, this article gives prospects for the synthesis and application of catalysts in different pathways. Graphical abstract: The conversion of perchlorate into innocuous chloride ions is tough. This review presents recent advances in catalytic hydrogenation and oxygen transfer reaction for accelerating perchlorate reduction. Image 1 Highlights: Recent advances in catalysis reduction for perchlorate are overviewed. Homogeneous, heterogeneous, electro- and bio-catalysis systems are discussed respectively. The mechanism and main factors of catalytic hydrogenation and OAT reaction are evaluated. The characteristic and application of different catalytic reactors are illustrated.